2015
DOI: 10.1007/s00213-015-3922-1
|View full text |Cite
|
Sign up to set email alerts
|

ITI-007 demonstrates brain occupancy at serotonin 5-HT2A and dopamine D2 receptors and serotonin transporters using positron emission tomography in healthy volunteers

Abstract: RationaleCentral modulation of serotonin and dopamine underlies efficacy for a variety of psychiatric therapeutics. ITI-007 is an investigational new drug in development for treatment of schizophrenia, mood disorders, and other neuropsychiatric disorders. ObjectivesThe purpose of this study was to determine brain occupancy of ITI-007 at serotonin 5-HT 2A receptors, dopamine D 2 receptors, and serotonin transporters using positron emission tomography (PET) in 16 healthy volunteers. MethodsCarbon-11-MDL100907, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Individuals randomized to 120 mg ITI-007 or risperidone received a single day dose titration (60 mg to 120 mg ITI-007 on day 2; 2 mg to 4 mg risperidone on day 2); 60 mg ITI-007 required no dose titration. Doses of 60 mg and 120 mg ITI-007 were selected based on estimated striatal D 2 receptor occupancy of approximately 50% and 70%, respectively, modeled from the D 2 receptor occupancies determined in a positron emission tomography study at lower doses in healthy volunteers (14). A dose of risperidone of 4 mg was selected as a positive control for assay sensitivity based on its mean modal effective dose determined by the Clinical Antipsychotic Trials of Intervention Effectiveness (15) and its well-characterized efficacy and safety profile as one of the most prescribed antipsychotics in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals randomized to 120 mg ITI-007 or risperidone received a single day dose titration (60 mg to 120 mg ITI-007 on day 2; 2 mg to 4 mg risperidone on day 2); 60 mg ITI-007 required no dose titration. Doses of 60 mg and 120 mg ITI-007 were selected based on estimated striatal D 2 receptor occupancy of approximately 50% and 70%, respectively, modeled from the D 2 receptor occupancies determined in a positron emission tomography study at lower doses in healthy volunteers (14). A dose of risperidone of 4 mg was selected as a positive control for assay sensitivity based on its mean modal effective dose determined by the Clinical Antipsychotic Trials of Intervention Effectiveness (15) and its well-characterized efficacy and safety profile as one of the most prescribed antipsychotics in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…4). Clinical studies in healthy volunteers using positron emission tomography revealed that lumateperone displayed high occupancy of the 5-HT 2A R in the cortex and negligible occupancy of the D 2 striatal receptors [118], suggesting that it is less likely to induce extrapyramidal side effects. Lumateperone has a unique mechanism of action, modulating synergistically multiple neurotransmitter systems, and has been suggested as a potential treatment for a range of neuropsychiatric disorders [73].…”
Section: Novel Atypical Antipsychoticsmentioning
confidence: 99%
“…Clozapine is an exception with relatively low striatal D 2 receptor occupancy (<60%) at antipsychotic doses and a low liability for parkinsonism, akathisia, and hyperprolactinemia [152, 174, 183, 185, 186]. At a low single dose of 10 mg in healthy volunteers, ITI-007 demonstrated low (~12%) striatal D 2 receptor occupancy and high (>80%) cortical 5-HT 2A receptor occupancy [156]. ITI-007 demonstrated an average of 29% (peak of 39%) D 2 occupancy at the highest evaluated dose in healthy volunteers.…”
Section: Comparison Of Representative Antipsychotics Haloperidol CLmentioning
confidence: 99%
“…These clinical observations suggest that ITI-007 is not associated with the usual side effects of existing medications for schizophrenia. An effective dose of 60 mg ITI-007 is associated with approximately 40% striatal D 2 receptor occupancy, substantially lower than that required by other antipsychotic drugs [125, 156]. This sparing of D 2 receptor occupancy likely contributes to ITI-007’s reduced liability for motor side effects and hyperprolactinemia.…”
Section: Comparison Of Representative Antipsychotics Haloperidol CLmentioning
confidence: 99%